Congenital hypothyroidism – An usual suspect at an unusual age: A case series - Sukumar, Suja P. (Medknow Publications & Media Pvt Ltd, 2013)
Menorrhagia is the most common menstrual irregularity in hypothyroid women. However, it is an uncommon presentation of congenital hypothyroidism (CH). In the era of newborn screening across the world, when CH is extremely rare, we came across four cases of CH due to delayed diagnosis, presenting in adulthood with severe menorrhagia. AIMS: To signify the atypical presentation of CH in late adulthood due to delayed diagnosis and its sequelae; and to increase the awareness about this treatable condition. SETTINGS AND DESIGN: This is a cross-sectional analysis of consecutive patients with CH presenting after 18 years between 2010 and 2012 from the CH registry of Department of Endocrinology, Jawaharlal Institute of Postgraduate Medical Education and Research (JIPMER), India. SUBJECTS AND METHODS: Four patients of CH presenting late (>18 years) with atypical presentations out of total 16 cases of CH within a period of 3 years were analyzed for clinical, hormonal, and imaging findings. RESULTS: Between the years 2010 and 2012, 16 cases of CH were registered at our center out of which four cases presented in late adolescence and adulthood with menorrhagia. Age range of these patients was 18-30 years. All four patients were females presenting with anemia secondary to menorrhagia and upon evaluation were found to have CH. All of them showed improvement after starting treatment and are currently doing well with regular menstrual cycles. CONCLUSIONS: Our study demonstrates the importance of thyroid evaluation in a patient presenting with menorrhagia along with short stature. There is need for awareness among clinicians regarding the clinical features of CH and nationwide screening for CH in our country.